How Green Marketing Builds Consumer Intention: A Study on the Mediating Role of Green Perceived Value and Green Trust in Organic Agricultural Product Purchases - Eriklex Donald; Abdullah, Muhamad Al Faruq (Dinasti Review, 2025)
This study is titled “How Green Marketing Builds Consumer Intention: A Study on the Mediating Role of Green Perceived Value and Green Trust in Organic Agricultural Product Purchases.” It aims to examine the influence of green marketing strategies on consumer purchase intention of organic agricultural products by considering the mediating roles of green perceived value and green trust. The study employs a quantitative approach using a survey method with 180 respondents who have purchased or considered purchasing organic products in modern traditional markets in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that green marketing has a positive and significant effect on green perceived value and green trust. Both mediating variables also have a significant influence on purchase intention. Furthermore, green perceived value and green trust significantly mediate the relationship between green marketing and purchase intention. The study concludes that effective green marketing strategies not only enhance consumer value perceptions and trust but also strengthen consumer purchase intention toward organic agricultural products. These findings contribute to the development of sustainable marketing strategies in the agribusiness and eco-based SME sectors.